Urbanization causes nonstationarity in Indian Summer Monsoon Rainfall extremes. Issue 21 (12th November 2016) - Singh, Jitendra; Vittal, H.; Karmakar, Subhankar; Ghosh, Subimal; Niyogi, Dev
Abstract: Global and local environmental changes are likely to introduce nonstationarity in the characteristics of Indian Summer Monsoon Rainfall (ISMR) extremes. Here we perform a nonstationary frequency analysis on ISMR extremes in a Generalized Additive Model for Location, Scale and Shape framework with a cluster of 74 models, considering nonstationarity in different possible combinations. Interestingly, we observe significant nonstationarity in ISMR extremes in urbanizing/developing‐urban areas (transitioning from rural to urban), compared to completely urbanized or rural areas. This presents a postulation that the extent of urbanization plays a significant role in introducing nonstationarity in ISMR extremes. We emphasize the effect of urbanization in changing the character of ISMR extremes, which further needs a scientific re‐evaluation by implementing physics‐based modeling. The impact of these observational studies will be critical in correcting the bias of model projections of ISMR. Key Points: Signature of nonstationarity in rainfall extremes is more significant in the developing‐urban areas than in the urbanized and rural areas Extent of urbanization plays a significant role in introducing nonstationarity in Indian Summer Monsoon Rainfall extremes A framework with a cluster of 74 nonstationary models is proposed to capture both linear and nonlinear changing characteristics of rainfall